Assessment of the Scholastic Performance and Cognitive Functions in Malnourished Children of Primary and Secondary Class Students - J. U. Senthamizhan; P. G. Rajakumar; Rathinasamy Muthusamy (Journal of the Scientific Society)
Background: Malnutrition is the consequence of a combination of deficiencies in protein, carbohydrates, and micronutrients. It includes undernutrition, overnutrition, and micronutrient deficiencies. Malnutrition is associated with both structural and functional pathology of the brain and reflects in poor scholastic performance and less cognitive functions in children. Aim: The aim of the study was to assess the scholastic performance and cognitive functions in malnourished children of primary and secondary classes studying in a school. Methodology: The study was conducted on 375 school children of primary and secondary classes. The nutritional status was assessed using the World Health Organization growth charts and classified based on their weight, height, and body mass index with malnutrition considered with values <−2 standard deviation for the age group. The scholastic performance was assessed using the school annual examination records and classified as good or poor scholastic performance with cutoff mark criteria of 50%. The cognitive function was assessed using the child mini–mental state examination (MMSE) test with the mean score for the age group. The scholastic performance and cognitive function were compared between the normal and malnourished groups. The variables were compared with respect to age, gender, standard, and P value obtained to see its significance. The variables were compared between the two groups in each class and test results were obtained. The correlation between each of the variables was also done. Results: Malnourished children were more in the primary classes (30%) than the secondary classes (13.2%). The scholastic performance in the normal group was increased than the malnourished group in both primary and secondary classes. The cognitive function based on the child MMSE score was also more in the normal group than in the malnourished group in both primary and secondary classes. There was a positive correlation between scholastic performance and cognitive function. Conclusion: The study results showed that the scholastic performance and cognitive function were decreased in the malnourished group than the normal group in both primary and secondary classes, implying that malnutrition affects the functionality of the brain and can cause long-term effects like poor cognition.